2017
DOI: 10.4251/wjgo.v9.i1.37
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial-mesenchymal transition as a therapeutic target for overcoming chemoresistance in pancreatic cancer

Abstract: Pancreatic cancer has one of the worst prognoses among all cancers due to the late manifestation of identifiable symptoms and high resistance to chemo- and radiation therapies. In recent years, a cancer development phase termed epithelial-mesenchymal transition (EMT) has gained increasing research focus. The process is implicated in tumour metastasis, and emerging evidence suggests EMT also contributes or induces chemoresistance in several cancers. Nevertheless, the applicability of therapeutic targeting of EM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 32 publications
1
36
0
1
Order By: Relevance
“…The viewpoint was supported by the findings in the study by Ren et al, who suggested that targeted inhibition of ZEBl in pancreatic cells can restore epithelial cell characteristics, and enhance the sensitivity of antitumor drugs. Moreover, recent clinical studies have shown that EMT‐targeted therapeutic strategies can reverse cancer resistance to the chemotherapeutic drug, including carboplatin and gemcitabine …”
Section: Discussionmentioning
confidence: 99%
“…The viewpoint was supported by the findings in the study by Ren et al, who suggested that targeted inhibition of ZEBl in pancreatic cells can restore epithelial cell characteristics, and enhance the sensitivity of antitumor drugs. Moreover, recent clinical studies have shown that EMT‐targeted therapeutic strategies can reverse cancer resistance to the chemotherapeutic drug, including carboplatin and gemcitabine …”
Section: Discussionmentioning
confidence: 99%
“…found that the expression of p21 is up‐regulated and phosphorylated (p‐) AKT is down‐regulated through inhibition of Skp2, thereby preventing the progression of tumour. EMT is considered to be closely related to invasion and metastasis of gliomas . The activation of EMT involves various molecular and signal transduction pathways.…”
Section: Anticancer Activities Of Paeoniflorin and Its Potential Mechmentioning
confidence: 99%
“…EMT is considered to be closely related to invasion and metastasis of gliomas. [64][65][66][67] The activation of EMT involves various molecular and signal transduction pathways. It has been proved that transforming growth factor-b (TGF-b) and MMP2/9 are a kind of key cytokine, which are closely related to the invasion, proliferation and angiogenesis of gliomas.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…Thus, since the EMT process is crucial for cancer-enhanced invasion, metastasis, chemoresistance, and survival, it is now the target of different experimental therapeutic approaches [3][4][5]. However, even though the role of EMT in the pathogenesis of cancer transformation has been proven in vitro and in vivo, its translation to the clinic has failed in most cases.…”
Section: Specificities Of Tumor Emtmentioning
confidence: 99%
“…In this sense, there is growing evidence suggesting that targeting EMT can be used as a therapeutic approach itself, or to enhance the efficacy of other anticancer treatments [3][4][5].…”
Section: Introductionmentioning
confidence: 99%